If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4x + 3) = 2 Reorder the terms: 2(3 + 4x) = 2 (3 * 2 + 4x * 2) = 2 (6 + 8x) = 2 Solving 6 + 8x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 8x = 2 + -6 Combine like terms: 6 + -6 = 0 0 + 8x = 2 + -6 8x = 2 + -6 Combine like terms: 2 + -6 = -4 8x = -4 Divide each side by '8'. x = -0.5 Simplifying x = -0.5
| 4x-15=x+10 | | 5x-12=2x-9 | | 2H+4S=22 | | 5(x-3)=-13 | | 19-x+4+x+19+x-1=34 | | 3x=1.08 | | F(x)=(radx-2)-3 | | ln(3-7x)=-2 | | 3x+1.66=1.8 | | 10x^3+58x^2+43x-11=0 | | 10x^3+58x^2+43x-11=f(x) | | 24x=-16x^2+6 | | 5x-7y=29 | | 5cos(x)=0 | | 0.04*0.8= | | x+(2x+15)=150 | | 0.75d-0.67d=0.67+6 | | 88+5x= | | K-(-6)=-33 | | x+0.5x+0.25x+1=100 | | x+(2x-15)=150 | | x+0.5x+0.75x+1=100 | | 6x-2=64(2x) | | 5+2+x=9 | | 4x=12-x | | sin*2*t= | | 3y+3=6(y+1) | | (2x+5)+(2x+2)=4(x-1)+9 | | (5-2x)(2x+1)=4x^2-25 | | (y+1)(y-2)= | | 3m/7=9 | | (5-2x)(2x+7)=4x^2-25 |